The Role of Digital Marketing and Discounts in Purchase Intention on Tiktok Live Sales - Rimel Levani Clarensa; Sabar Narimo (Dinasti Publisher, 2025)
This study aims to examine the influence of digital marketing and discounts on purchase intention during TikTok live sales. The rapid development of social media has transformed how companies market their products. TikTok, as one of the most popular platforms today, functions not only as a medium of entertainment but also as a tool for promotion and direct selling through its TikTok Live Sale feature. Through this feature, sellers can interact directly with potential buyers and offer attractive promotions such as price reductions or discounts to increase purchase intention. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 121 TikTok users in Indonesia. Data analysis was conducted using SmartPLS 3.0 with the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The results indicate that digital marketing has a positive but insignificant effect on purchase intention, suggesting that digital promotional activities such as social media content, online advertising, or live streaming have not been able to directly increase consumers’ willingness to purchase. In contrast, discounts have a positive and significant effect on purchase intention, meaning that the greater the price reduction offered, the higher consumers’ intention to buy products during live sales.